Penegakan Hukum Tata Ruang Atas Pembangunan Pariwisata Di Sempadan Pantai (Studi Kasus Pantai Bingin Bali) - Putu Wahyu Widiartana; Komang Arya Mukti Maruti; Ni Putu Ega Maha Wiryanthi (Kertha Wicaksana, 2025)
This article examines the enforcement of spatial planning law by the Badung Regency Government in controlling the development of tourism accommodations within the beach border area of Pantai Bingin, Bali. It highlights the issue of illegal buildings that violate the Rencana Tata Ruang Wilayah (RTRW) and Peraturan Daerah, threatening the ecological sustainability of coastal areas and restricting public access to the beach. Using a normative legal research method with a statutory and conceptual approach, this article aims to analyze the effectiveness of existing law enforcement mechanisms and identify the factors hindering their optimal implementation. The focus of the study is directed at the implementation of spatial planning law enforcement by the Badung Regency Government through the application of the RTRW and Peraturan Daerah in the beach border area for the development of tourism accommodations at Pantai Bingin, Bali, as well as the factors influencing the effectiveness of local regulation enforcement officers in efforts to protect coastal areas. The findings of this research are expected to contribute to strengthening spatial planning law enforcement to protect coastal zones as sustainable public spaces.